The clinical application of longitudinal layer specific strain as a diagnostic and prognostic instrument in ischemic heart diseases: A systematic review and meta-analysis - Sharma, Shreeya; Lassen, Mats Christian Højbjerg; Nielsen, Anne Bjerg; Skaarup, Kristoffer Grundtvig; Biering-Sørensen, Tor (Frontiers in Cardiovascular Medicine, 2023)
Background 2-dimensional Speckle-Tracking Echocardiography, to obtain longitudinal layer specific strain (LSS), has recently emerged as a novel and accurate non-invasive imaging technique for diagnosis as well as for prediction of adverse cardiac events. This systematic review and meta-analysis aimed to give an overview of the possible clinical implication and significance of longitudinal LSS. Methods We conducted a systematic review and meta-analysis with all the studies involving layer specific strain in patients with ischemic heart disease (IHD). Of 40 eligible studies, 9 met our inclusion criteria. Studies that were included either investigated the prognostic value (n = 3) or the diagnostic value (n = 6) of longitudinal LSS. Results The pooled meta-analysis showed that longitudinal LSS is a significant diagnostic marker for coronary artery disease (CAD) in patients with IHD. Endocardial LSS was found to be a good diagnostic marker for CAD in IHD patients (OR: 1.28, CI95% [1.11–1.48], p < 0.001, per 1% decrease). Epicardial (OR: 1.34, CI95% [1.14–1.56], p < 0.001, per 1% decrease), Mid-Myocardial (OR: 1.24, CI95% [1.12–1.38], p < 0.001, per 1% decrease) and endocardial (OR: 1.21, CI95% [1.09–1.35], p < 0.001, per 1% decrease) LSS all entailed diagnostic information regarding CAD, with epicardial LSS emerging as the superior diagnostic marker for CAD in patients with SAP. Endocardial LSS proved to be the better diagnostic marker of CAD in patients with non-ST elevation acute coronary syndrome (NSTE-ACS). LSS was shown to be a good prognostic maker of adverse cardiac events in IHD patients. Two studies found endocardial circumferential strain to be the good predictor of outcome in CAD patients and when added to baseline characteristics. Epicardial LSS emerged as best predictor in acute coronary syndrome (ACS) patients. Conclusion In patients with SAP, epicardial LSS was the stronger diagnostic marker while in NSTE-ACS patients, endocardial LSS was the stronger diagnostic marker. In addition, endocardial circumferential strain is the better predictor of adverse outcome in CAD patients whilst in ACS patients, epicardial LSS was found to be a better predictor of outcome.